The Influence of PAK Teachers' Example on the Personality of Class VIII Students of SMP Negeri 3 Tarutung, North Tapanuli Regency for the 2023/2024 Academic Year - Lilis Suganda Sihotang; Taripar Aripin Samoir; Damayanti Nababan (STIKes Ibnu Sina Ajibarang, 2023)
The purpose of this study was to determine the influence of the example of PAK teachers on the personality of grade VIII students at SMP Negeri 3 Tarutung, North Tapanuli Regency for the 2023/2024 academic year. The method used in this study is a quantitative research method with descriptive and inferential statistical approaches. The population is all grade VIII students of SMP Negeri 3 Tarutung, North Tapanuli Regency for the 2023/2024 academic year who are Christians, totaling 180 people and a sample of 54 people was determined from the total population using the proportional random sampling technique according to strata (Proportionate Staratifiet Random Sampling). Data was collected with a positive closed questionnaire of 46 items where 26 items were for variable X and 20 items for variable Y. The results of the data analysis showed that there was a positive and significant influence on the role model of PAK teachers on the personality of grade VIII students at SMP Negeri 3 Tarutung, North Tapanuli Regency for the 2023/2024 academic year: 1) Influence Test: obtained regression equation Y ̂=32.38+0.49X.b) From the linear regression test, it can be proven that the influence of variable X (PAK Teacher Example) on variable Y (Student Personality) is positive because the regression coefficient (β) = 0.49, Furthermore, the t test to test the significance of the regression coefficient (B) obtained tcalculate = 5.008 > ttable which is 2.000. Thus, Ha is that there is a positive and significant influence on the role model of PAK teachers on the personality of grade VIII students at SMP Negeri 3 Tarutung, North Tapanuli Regency for the 2023/2024 academic year, accepted and H0 rejected.